A determination of the Planck constant by the generalized joule balance method with a permanent-magnet system at NIM. (13th January 2016) - Xu, Jinxin; Zhang, Zhonghua; Li, Zhengkun; Bai, Yang; Wang, Gang; Li, Shisong; Zeng, Tao; Li, Chen; Lu, Yunfeng; Han, Bing; Wang, Nong; Zhou, Kunli
Abstract: The joule balance experiment has been carried out at the National Institute of Metrology, China (NIM) since 2007. By the end of 2013 the first generation of the joule balance (NIM-1) achieved a measurement uncertainty of 7.2 × 10 −6 ( k = 1). To reduce the measurement uncertainty further, the next generation of the joule balance apparatus (NIM-2) system is under construction. A new coil system using ferromagnetic material is being adopted in NIM-2 to reduce self-heating in the coils. However, the effects on the measurement of the mutual inductance from the nonlinearity and hysteresis of the ferromagnetic material will bring a considerable measurement uncertainty. Inspired by the watt balance, the measurement of the mutual inductance is replaced by an equivalent measurement of the magnetic flux linkage difference. The nonlinearity and hysteresis will not be a problem in the measurement of the magnetic flux linkage difference. This technique comes from the watt balance method. It is called the generalized joule balance method, which is actually a modification of the watt balance method. However, it still represents a valid change that can reduce the difficulty of dynamic measurement experienced using the watt balance. Permanent magnets can also be adopted in the generalized joule balance. To check the feasibility of the generalized joule balance method, some preliminary experiments have been performed on NIM-1. A yokeless permanent magnet system has been designed and used to replace the exciting coils in NIM-1. In this paper, the structure of the yokeless permanent magnet system is introduced. Furthermore, a determination of the Planck constant with the permanent magnet system is presented. The value of the Planck constant h we obtained is 6.626 069(17) × 10 −34 J s with a relative standard uncertainty of 2.6 × 10 −6 .